Pneumocystis Prophylaxis for All, Some, or No HIV-infected Infants Less than One Year of Age: A Decision Analysis Approach - Upton D Allen; Stanley E Read (Canadian Journal of Infectious Diseases)
Pneumocystis carinii pneumonia (PCP) is associated with significant mortality and morbidity among infants infected with human immunodeficiency virus (HIV). The preferred prophylaxis strategy for such infants is a subject of debate. Medical decision analysis was used to determine the preferred strategy for primary PCP prophylaxis among asymptomatic HIV-infected infants less than one year of age, and to determine the thresholds at which different variables influence decision making. Utility measures (health state preference values) were used to determine whether prophylaxis should be given to all, some or no infants. In this regard, some infants would receive prophylaxis if baseline CD4 counts are fewer than 1500 cells/mm3. The results suggest that the preferred option is to give prophylaxis to all asymptomatic HIV-infected infants despite CD4 counts, if the risk of PCP is equal to or greater than 25%. However, if the risk of PCP is less than 25%, prophylaxis is recommended for those infants with CD4 counts of fewer than 1500 cells/mm3. The results complement current guidelines regarding PCP prophylaxis for HIV-infected infants.